Comparing the pain of propofol via different combinations of fentanyl, sufentanil or remifentanil in gastrointestinal endoscopy - Zhang,Lifeng (2014)
PURPOSE: To evaluate the pain on injection of propofol via different combinations of fentanyl, sufentanil or remifentanil in gastrointestinal endoscopy. METHODS: Total 439 patients were randomly allocated into 6 groups. Propofol & fentanil (PF) group received 1 μg/kg fentanyl, propofol & sufentanil (PS) group received 0.1 μg/kg sufentanil and propofol & remifentanyl (PR) group received 1 μg/kg remifentanyl prior to administration of 1-2 mg/kg of propofol. The propofol & half-fentanil (Pf) group, propofol & half-sufentanil (Ps) group and propofol & half-remifentanyl (Pr) group were given 0.5 μg/kg fentanyl, 0.05 μg/kg sufentanil and 0.5 μg/kg remifentanyl, respectively and later administrated 1-2 mg/kg propofol. All patients were monitored for the blood pressure (MAP), heart rate (HR), and oxygen saturation (SpO2). Additionally, the pain intensity was assessed using a 4-point verbal rating scale (VRS) by professional doctors. RESULTS: The incidence of pain due to propofol injection in Ps group (33.8%) was significantly lower than other 5 groups. The heart rate (HR) and mean arterial pressure (MAP) were maintained within the normal limits in all six groups and there was no hypotension or bradycardia encountered during the study period. CONCLUSION: Propofol and sufentanil group was the most suitable program for painless gastroscopy.